THE ROLE OF STRATEGIC INVESTMENTS IN THE DEVELOPMENT OF HUMAN CAPITAL AMID THE DIGITAL TRANSFORMATION OF UZBEKISTAN’S BANKING SYSTEM (Scientific electronic journal "Labor Economics and Human Capital", 2024)
This article examines the significance of strategic investments in the development of human capital amid the digital transformation of Uzbekistan’s banking system. The article emphasizes the role of employee training and retraining, as well as adaptation to new technologies, such as artificial intelligence and automation. The results and prospects of banking modernization through the development of employees' digital skills are analyzed, which contributes to increasing the productivity, competitiveness, and innovation capacity of the banking sector. Special attention is given to the implementation of modern human resource management methods and the development of strategies to retain qualified specialists in the context of global competition.
Keywords: Human capital, digital transformation, banking ecosystem, investments, training, retraining, talent management, artificial intelligence.